Distinct Dysfunctional States of Circulating Innate-Like T Cells in Metabolic Disease - Li, Yanyan; Woods, Katherine; Parry-Strong, Amber; Anderson, Regan J.; Capistrano, Celina; Gestin, Aurelie; Painter, Gavin F.; Hermans, Ian F.; Krebs, Jeremy; Gasser, Olivier (Frontiers in Immunology, 2020)
The immune system plays a significant role in controlling systemic metabolism. Innate-like T (ILT) cells in particular, such as mucosal-associated invariant T (MAIT) cells, invariant natural killer T (iNKT) cells and gd T cell receptor expressing cells, have been reported to promote metabolic homeostasis. However, these different ILT cell subsets have, to date, been generally studied in isolation. Here we conducted a pilot study assessing the phenotype and function of circulating MAIT, iNKT and Vd2+ T cells in a small cohort of 10 people with obesity and type 2 diabetes (T2D), 10 people with obesity but no diabetes, and 12 healthy individuals. We conducted phenotypic analysis by flow cytometry ex vivo, and then functional analysis after in vitro stimulation using either PMA/ionomycin, or prototypical synthetic agonists for each of the cell-types; use of the latter may provide important knowledge for the development of novel therapeutics aimed at activating human ILT cells. The results of our pilot study, conducted on circulating cells, show clear dysfunction of all three ILT cell subsets in obese and obese T2D patients, as compared to healthy controls. Importantly, while both iNKT and Vd2+ T cell dysfunctions were characterized by diminished IL-2, IL-4 and interferon-g production, the distinct dysfunctional state of MAIT cells, which additionally featured skewed subset composition, was instead defined by heightened sensitivity to T cell receptor engagement and a trend towards increased cytokine production.